1992
DOI: 10.1128/jcm.30.2.465-472.1992
|View full text |Cite
|
Sign up to set email alerts
|

Development of a polymerase chain reaction-based diagnosis of Trichomonas vaginalis

Abstract: We developed a polymerase chain reaction (PCR)-based test for detecting the protozoan parasite Trichomonas vaginalis. Genomic libraries were constructed from two independent clinical isolates of T. vaginalis. From these libraries, 12 genomic clones were purified, sequenced, and then screened for uniqueness by computerassisted sequence comparisons. PCR reactions were performed to evaluate eight PCR-primer pairs, including a primer pair that targeted the T. vaginalis ferredoxin gene. All eight primer pairs yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 56 publications
0
51
0
2
Order By: Relevance
“…74 With the increasing incidence of metronidazole resistance, 112 cultures may become more standard practice. 2 Several other methods are also being evaluated for the diagnosis of trichomonas infection, including a polymerase chain reaction-based test, 26,113 a direct fluorescent antibody test, and an enzyme immunoassay. 110 Sensitivities and specificities of these tests, however, are not clearly established.…”
Section: Diagnosismentioning
confidence: 99%
“…74 With the increasing incidence of metronidazole resistance, 112 cultures may become more standard practice. 2 Several other methods are also being evaluated for the diagnosis of trichomonas infection, including a polymerase chain reaction-based test, 26,113 a direct fluorescent antibody test, and an enzyme immunoassay. 110 Sensitivities and specificities of these tests, however, are not clearly established.…”
Section: Diagnosismentioning
confidence: 99%
“…We confirmed the band of 638 bp, as in their report. This might be of interest since we achieved successful results suggesting that the Papanicolaou-stained smear offers a reliable source for DNA diagnosis, which may obtain a higher level of diagnosis when we used the PCR method of Rappelli et al 13 together with the method of Riley et al 12 In summary, this study demonstrated that PCR for the detection of T. vaginalis DNA in cytological archival smears could be particularly useful in assessing the presence of T. vaginalis in those patients in whom the cytologic findings on Papanicolaou-stained smears are thought to be equivocal. Further cytodiagnostic applications of this established PCR assay might involve reevaluation of cervical smears in retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PCR to successfully diagnose T. vaginalis infection was first reported in 1992 by Riley et al 12 They studied T. vaginalis DNA isolation, and tested PCR amplification. This PCR amplification was carried out with primers targeting the A6p sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the available formats for the molecular diagnosis of T. vaginalis, the Xpert TV assay (Cepheid, Sunnyvale, CA) has improved the diagnostic capability and is a US-FDA approved NAAT for use in both females and males (Schwebke et al 2018). Polymerase chain reaction (PCR) targeting the 18S rRNA, beta-tubulin, and adhesin genes of T. vaginalis, has also shown promising results (Riley et al 1992;Madico et al 1998). With the advent of a loop-mediated isothermal amplification (LAMP) assay for the rapid detection of T. vaginalis, a higher analytical sensitivity of 42% compared with culture (8Á26%) and conventional PCR (7Á44%) has been reported (Adao and Rivera, 2016).…”
Section: Introductionmentioning
confidence: 99%